Regional Bank Efficiency and its Effect on Regional Growth in Normal and Bad Times - Ulrich Haskamp; Ralph Setzer; Ansgar Belke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The financial crisis affected regions in Europe in a different magnitude. We examine whether regions which incorporate banks with a higher intermediation quality grow faster using a sample which includes the aftermath of the financial crisis. We measure the intermediation quality of a bank by estimating a its profit and cost efficiency. Next, we aggregate the efficiencies of all banks within a NUTS 2 region to obtain a regional proxy for financial quality in twelve European countries. Our results show that relatively more profit efficient banks foster the economic growth in their region. The link between financial quality and growth is valid in normal times as well as in bad ones.
Keywords: G21; O47; O52; 330